High-volume intensive training course: a new paradigm for video-assisted thoracoscopic surgery education. (27th March 2018) - Sihoe, Alan D L; Gonzalez-Rivas, Diego; Yang, Timothy Y; Zhu, Yuming; Jiang, Gening
Abstract: OBJECTIVES: The emergence of ultra-high-volume centres promises new opportunities for thoracic surgical training. The goal of this study was to investigate the effectiveness of a novel observership course in teaching video-assisted thoracoscopic surgery (VATS) at an ultra-high-volume centre. METHODS: Two-week courses in VATS at a specialist unit now performing >10 000 major lung resections annually (>50 daily on average) were attended by 230 surgeons from around the world from 2013 to 2016. An online survey preserving responder anonymity was completed by 156 attendees (67.8%). RESULTS: Attendees included 37% from Western Europe, 18% from Eastern Europe and 17% from Latin America. Experience with open thoracic surgery for more than 5 years was reported by 67%, but 79% had less than 5 years of VATS lobectomy experience. During the course, 70% observed over 30 uniportal VATS operations (including 38% observing over 50), and 69% attended an animal wet lab. Although 72% of the responders attended the course less than 12 months ago, the number of ports used ( P < 0.001), operation times ( P < 0.001) and conversion rates ( P < 0.001) reported by the responders were reduced significantly after the course. Improvements in the problem areas of tissue retraction, instrumentation, stapler application and coordination with the assistant during VATS were reported by 56%, 57%, 58% and 53%, respectively. Of those who had attended other VATS courses previously, 87% preferred the training from this high-volume course. CONCLUSIONS: High-volume intensive observership training at an ultra-high-volume centre may improve VATS proficiency in a short period of time, and may provide a time-efficient modality for future thoracic surgical training.